Structural and optical properties of CdS:Sn thin films prepared by chemical spray pyrolysis method - Nadia Jasim Ghdeeb (Iraqi Journal of Physics, 2019)
CdS and CdS:Sn thin films were successfully deposited on glass substrates by spray pyrolysis method. The films were grown at substrate temperatures 300 C°. The effects of Sn concentration on the structural and optical properties were studied. The XRD profiles showed that the films are polycrystalline with hexagonal structure grown preferentially along the (002) axis. The optical studies exhibit direct allowed transition. Energy band gap vary from 3.2 to 2.7 eV.